Family's Experience Dealing with Critical Patient Hospitalization in the Intensive Care Unit - Maria Theresia Dhiu; Ninuk Dian Kurniawati; Andri Setya Wahyudi (Universitas Airlangga, 2021)
Introduction: The Intensive Care Unit (ICU) is a treatment that can cause feelings of stress, anxiety, and fear not only in the patient but also in the patient's family. The unfamiliar environment, intensive space regulation, changes in emotional status, and changes in daily activities cause stress in the ICU patient's family. The purpose of this study is to reveal the experiences of families facing hospitalization in intensive care units based on empirical studies in the last five years. Methods: Journal searches use indexed databases Scopus, Proquest, ScienceDirect, and PubMed using keywords: hospitalization, family, critical patient, ICU. The Center for Review and Dissemination and The Joanna Briggs Institute were used to assess the quality of the study. The framework used is PICOS with inclusion criteria, namely journals in English and Indonesian, published years 2015 to 2020. Analyzes and tabulation of data on articles or journals, titles, abstracts, full text, and methodology are assessed to determine the eligibility of articles or journals. Result: The family's experience in critical patient hospitalization in the ICU care room impacts the family's treating these patients physically and psychologically. During patient hospitalization, the family plays a role in providing care, and compassion, creating security and privacy, and advocating for and ensuring that patients receive good care. Conclusion: The hospitalization experience can disrupt the client's psychology and psychosocial condition, especially if the client cannot adapt to his new environment at the hospital. The patient must have a vital source of support to support healing. One of these supports can be obtained from the patient's family.